Kritik Arsitektur terhadap Aspek Inklusif Aksesibilitas Hubungan Horizontal Antar Ruang atau Antar Bangunan Studi Kasus: Selasar RSP (Rumah Sakit Paru) Dr. H. A. Rotinsulu Bandung - Kusmana, Tresna Lugina; Widaningsih, Lilis; Ilhamdaniah, Ilhamdaniah (Jurnal Talenta Sipil, 2024)
Hallway of the Lung Hospital DR. H. A. Rotinsulu is one of the facilities that functions as the accessibility of relationships between spaces or between buildings. Tues as referred to in the Lung Hospital DR. H. A. Rotinsulu is a means of connecting circulation pathways between rooms or between buildings outside a building that is not limited by walls or limited by at most 1 (one) side wall. The object of Architectural Criticism is the hall of Dr. Lung Hospital. H.A Rotinsulu Bandung. Architectural criticism is carried out in the form of observations and measurements in the field on several walkway segments, based on the steepness of the contours that have been measured influenced by the long span of each walkway segment, which has been divided into observations according to the existing conditions of the walkways of Dr. Lung Hospital. H. A Rotinsulu Bandung, then a study was carried out in the form of an evaluation of the existing conditions of the walkway according to Ministerial Regulation PUPR No. 14 of 2017 concerning Requirements for Building Facilities and Law no. 8 of 2016 concerning Persons with Disabilities. The aspects studied are: 1. Needs for space for movement of users, 2. Circulation, 3. Guiding paths 4. Placement of gathering points, 5. Waiting area or right of way in transit to the hall rest. The basic dimensions of space and related facilities according to the object of observation refer to the Universal Design principle or the principle of inclusive design so that each user can move easily, safely, comfortably and independently.